Apoptotic Index Fails to Predict Chemoresponse in Breast Cancer - Siregar, Kamal Basri (Sumatera Medical Journal, 2019)
The responsiveness of neoadjuvant chemotherapy in Triple Negative Breast Cancer (TNBC) needs determination to prevent overtreatment with chemoresistance regimen. A total of 60 consented patients from Haji Adam Malik and Bunda Thamrin Hospital were included in this cohort prospectie study. Patients with heart, kidney, liver disease, history of surgery, chemotherapy, or hormonal therapy were excluded. Apoptotic indexes were taken from all subjects before and after neoadjuvant chemotherapy. After 3 cycles of neoadjuvant chemotherapy, 31 subjects (51.7%) did not show clinical response while 29 subjects (48.3%) had clinical response. There was no significant difference of apoptotic index before and after neoadjuvant chemotherapy (5.47+1.38 vs 5.52+1.08 pg/mL). There was also no significant relationship between apoptosis index and clinical response (p=0.993). This study showed that apoptotic index fails to be neoadjuvant chemotherapy response predictor in triple negative breast cancer. Further research with larger samples is needed to confirm this result